Life will begin again - Lim, Chessa Shi En (2015)
Life Will Begin Again takes viewers into a dialogue between the fragility of the self in our existential realm and the workings of phenomena in the spiritual realm. It aims to ignite our consciousness of life through an art installation, drawing upon the fusion of biology and theology. Life Will Begin Again reflects on the way that hidden processes govern our lives: Internal and external, great and small, dying and growing, individual and social, cognitive and emotive, using the certain and unbroken electrical beating of our heart to bring us to a point of rendezvous with this order. It seeks to map out the work of an intelligent designer, the Lord God of the universe, through a cross disciplinary study of theology and biology. Life Will Begin Again is a project that hopes to bridge the understanding of theological studies with art, an area that is not often seen both in the art market and within the church. Through this project, I hope to bring into consensus amongst theologians and artists, a single possible methodology of bringing the bible together with contemporary art. Though Chessa specializes in Visual Communication, she desires to be an Artist.